P–735 Spontaneous pregnancies among infertile couples during assisted reproduction lockdown for COVID–19 pandemic. (6th August 2021) - Morini, D; Melli, B; Santi, D; Spaggiari, G; Citro, M C; Lutzoni, R; Simoni, M; Aguzzoli, L; Villani, M T
Abstract: Study question: Evaluate the population attending Assisted reproductive techniques (ART) who have suffered the interruption of fertilization paths because of the SARS-CoV–2 italian national lockdown declared under goverment provision. Summary answer: The research show that some infertile couples candidate to ART paths obtained a spontaneous pregnancy during the lockdown due to SARS-CoV–2 pandemic. What is known already: The real impact of psychological stress on couple infertility in terms of pregnancies obtained is largely under-investigated in the literature and the potential low frequency of sexual activity is usually poorly considered in the management of couple infertility and its role on pregnancies failure is unclear, but probably underestimated. Moreover, the worldwide spread of the SARS-CoV–2 infection has profoundly affected all aspects of human life, with tangible consequences in several contexts, including reproduction. This allowed to highlight the interrelation between psychological distress and reproductive medicine are still conflicting. Study design, size, duration: This is a study conducted at the Fertility Centre of the Department of Obstetrics and Gynaecology of Reggio Emilia (Italy), that evaluated the conception ability of couples who suffered the postponement of ART cycles during the SARS-CoV–2 pandemic. In particular, we collected anamnestic, anthropometrical and demographic data of those women attending ART straddling the lockdown period, from March 2020 to April 2020. Participants/materials, setting, methods: The study evaluated couples attending ART, who had an interruption of the fertilization paths due to the SARS-CoV–2 pandemic. The variables as women age, BMI, duration of infertility, number of sexual intercourses per week and infertility aetiology were considered in a multivariate logistic analysis. The statistical analysis was performed setting pregnancy (categorical data) as the dependent variable, and all other available data as either covariates or cofactors. Main results and the role of chance: Among the 431 couples recalled to reschedule ART cycles 34 couples (7.9%) obtained a spontaneous pregnancy during the COVID–19 lockdown. The statistical analysis for the 431 couples recalled showed that average duration of couple infertility was 3.5 ± 2.8 years, while an exclusively female causal factor was observed in the 23.7% of cases (102 couples), an exclusively male one in the 32.7% (141 couples), a coexistence of male/female factor in the 18.6% (80 couples), and an idiopathic form in the 25.1% (108 couples). The 34 couples obtained a spontaneous pregnancy presented a female infertility factor in the 26.5% of cases (9 couples), a male factor in the 29.4% (10 couples), a male/female factor in the 11.8% (4 couples), and idiopathic infertility in the 32.4% (11 couples). The male factor of infertility was not evaluated in all couples, thus this definition came from the anamnestic evaluation of the couple. In a multivariate logistic analysis we highlighted that the infertility history duration and the sexual intercourses frequency were significantly related to pregnancy (F = 4.8, degrees of freedom=1, p = 0.030 and F = 81.6, degrees of freedom=1, p < 0.001, respectively). Limitations, reasons for caution: Despite the short observation period (two months of italian national lockdown declared under goverment provision), the large sample size of women evaluated attending to a single ART centre constitutes a point of strength of our study. However, the absence of a control group represents the most important limit. Wider implications of the findings: In conclusion, the lockdown allowed to increase the knowledge about under-explored causes of idiopathic infertility: the frequency of sexual intercourses. This aspect in reproductive medicine could help to identify those couples able to conceive spontaneously, avoiding unnecessary over-treatment, and to correctly apply ART to those couples who really need it. Trial registration number: none